Solo un Cargador . Porter - Ramirez, Juan Alejandro (Ramirez, Juan Alejandro, 2003)
Duration: 00:30:00 "The deapths of the soul are farther away than the ends of the earth." This Nordic proverb is used as a motto for this meditative Peruvian film. The special rhythm of the footage of a porter of luggage for the tourist expeditions in the great mountains of Peru is accompanied by the director's own fictitious commentary. They stem from Juan Alejandro Ramirez's own experience with seasonal workers and is conceived as an internal monologue of the Peruvian porter Juan Manuel Orozco, nicknamed "Sad Face." "No one knows what tomorrow will be like but I am sure, it will look like today," the author pust these words into the mouth of Juan Orozco, who day after day hauls tourists' luggage on his back up the steep incline of the Peruvian Andes. The melancholic mood of the film is made more powerful by Chopin's piano music, which adds a strong existential charge. A very human film, which has receievd acclaim in several prestigious film festivals, and resembles in its formal features the raw poetry of Latin American cinematography.